Isolation and Evaluation of Clinically Important Acinetobacter Baumannii From Intensive Care Unit Samples - Mohamed Mowfik Sehree; Hanaa N. Abdullah; Amani M. Jasim (Journal of Techniques)
Acinetobacter baumannii is considered a critical healthcare problem for patients in intensive care units due to its high ability to be multidrug-resistant to most commercially available antibiotics. The current study is at aimed at isolating and identifying the clinical isolates of A. baumannii from different samples and investigating the antibiotic resistance of isolates. Isolation and diagnosis of bacteria were achieved by conventional techniques, including routine and selective culture media (Chrome agar), biochemical test, EPI 20E, and VITEK-2. These methods were basically considered as a gold standard for identification of A. baumannii infections from different clinical sources, and culture positive isolates were tested for antibiotic susceptibility using a modified Kirby–Bauer method. A total of 375 clinical specimens were collected from different infections in some hospitals in Mosul and Erbil cities/Iraq from Sep 2020 to Jan 2021. Overall, 41 isolates were identified as A. baumannii using conventional and biochemical methods, and then confirmed by VITEK-2 system. Our results established that only 41(14.4%) isolates were diagnosed as A. baumannii, and most of these isolates were from burns (36.5%), surgical wounds (34.1%), and sputum (14.6%). However, it was identified in CSF, blood, and urine samples with lower percentages (7.3%, 4.8%, and 2.4%, respectively). The clinical isolates of A. baumannii showed high to moderate resistance to Piperacillin (97.5%), Piperacillin/ Tazobactam., Ceftazidime (87.8%), Meropenem (85.3%), Tri/slphamethoxazole (82.9%), Levofloxacin (80.4%), Imipenem, Ciprofloxacin (78%), Gentamycin (75.6%), Amikacin (73.1%), Netilmicin (68.2%), Tobramycin (60.9%) and Tetracycline (31.7%). However, two antimicrobial agents which were Colistin and Tigecycline produced 0 and 2.4 % resistance to A. baumannii respectively, which were considered the most used choices to treat A. baumannii infections.